An Intelligent Characteristics Analyzer of PV Module - Biswas, Liton Kumar; Rahman, Md. Habibur; Haque, Saiful (Dhaka University Journal of Science, 2013)
This paper describes construction, development and testing of a low cost PV module characteristics analyzer. A computer-based, fully automatic characteristic analyzer has been designed and developed using locally available components. The system is capable of acquiring current and voltage of PV module by varying the operating point to draw the IV curve and to analyze the module characteristics. In this system, a Pico ADC-16 has been used to convert the analog data into digital. The module current and voltage is changed by using a transistor active load. The operating point of the active load has been changed by the analog output of a DAC and the DAC is driven by a digital counter. A driver program has been developed for the system using C language. Finally, the system was assembled and the characteristics of some PV modules of different power capacity have been studied. It is found that, the system is capable of finding characteristics of PV modules up to the capacity of 75Watt. Dhaka Univ. J. Sci. 61(1): 65-70, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15098